2007
DOI: 10.1007/s10886-007-9323-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Insect Herbivore and its Pupal Parasitoid Reflect Differences in Direct Plant Defense

Abstract: In nature, plants defend themselves by production of allelochemicals that are toxic to herbivores. There may be considerable genetic variation in the expression of chemical defenses because of various selection pressures. In this study, we examined the development of the small cabbage butterfly, Pieris rapae, and its gregarious pupal ectoparasitoid, Pteromalus puparum, when reared on three wild populations (Kimmeridge, Old Harry, Winspit) of cabbage, Brassica oleracea, and a Brussels sprout cultivar. Wild plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 55 publications
3
44
0
Order By: Relevance
“…For example, GS in B. oleracea cultivars are often reduced compared with wild conspecific plants (Kushad et al 1999;Rosa 1999;Moyes et al 2000). Several studies have demonstrated that both herbivores and their parasitoids perform more poorly on wild than on cultivated brassicaceous plant species Harvey et al 2007a;Gols et al 2008c). …”
Section: Plant-herbivore-parasitoid Interactions In Domesticated and mentioning
confidence: 99%
“…For example, GS in B. oleracea cultivars are often reduced compared with wild conspecific plants (Kushad et al 1999;Rosa 1999;Moyes et al 2000). Several studies have demonstrated that both herbivores and their parasitoids perform more poorly on wild than on cultivated brassicaceous plant species Harvey et al 2007a;Gols et al 2008c). …”
Section: Plant-herbivore-parasitoid Interactions In Domesticated and mentioning
confidence: 99%
“…Transcription of MAM-like genes results in elongation of glucosinolate side chains from three carbon atoms (C 3 ) to C 4 , and up to C 8 , thereby affecting the ratio of, for example, C 3 to C 4 compounds in the glucosinolate profile (Kroymann et al 2001, Field et al 2004. The history of cultivation of B. oleracea has resulted in a decrease in total glucosinolate levels compared to wild type plants (Harvey et al 2007, Gols et al 2008a. However, cultivation has also led to a diversity of chemical profiles, with cultivars having relatively similar total concentrations of glucosinolates but different mixtures of C 3 and C 4 compounds in their profile.…”
Section: Introductionmentioning
confidence: 99%
“…Foliar glucosinolate concentrations measured as constitutive and herbivore-induced traits, as well as herbivore and parasitoid development have been studied in several wild B. oleracea populations and in a domesticated cultivar (Harvey et al 2007;Gols et al 2008a, b). Based on this information, we have selected two wild populations (Old Harry and Kimmeridge) and a cultivar and studied their inXuence on herbivore immune responses.…”
Section: Introductionmentioning
confidence: 99%